The low enoyl-acyl carrier protein reductase activity of FabI2 is responsible for the high unsaturated fatty acid composition in Sinorhizobium meliloti - Ya-Hui Mao; Feng Li; Li-Zhen Luo; Yu Yin; Jin-Cheng Ma; Wen-Bin Zhang; Hai-Hong Wang; Changyi Zhang; Zhe Hu (BMC Microbiology)
Abstract Background Sinorhizobium meliloti is noted for its exceptional capacity to produce unsaturated fatty acids (UFAs). Earlier studies have indicated that S. meliloti primarily employs the FabA-FabB pathway for UFA synthesis, however, the mechanisms remain elusive. This study was conducted to elucidate these mechanisms responsible for the significant UFA production in S. meliloti. Methods The genes encoding enoyl-acyl carrier protein (ACP) reductase (ENR) were disrupted using the suicide plasmid pK18mobsacB, followed by the creation of single-crossover and double-crossover mutants. The ENR proteins were expressed in Escherichia coli BL21(DE3) strains and subsequently purified. Their enzymatic activities were assessed through gel electrophoresis and NADH oxidation assays. Additionally, the fatty acid composition was determined using gas chromatography-mass spectrometry (GC-MS) and thin-layer chromatography. Results Our findings demonstrate that the heterologous expression of fabI2 in a temperature-sensitive E. coli fabI mutant results in a significant enhancement of UFA production. Genetic analyses confirmed that fabI2 is an indispensable gene in the S. meliloti genome, as it cannot be disrupted. Interestingly, we observed that fabI2 could only be functionally replaced by the Enterococcus faecalis fabI gene and not by the homologous fabI1 from S. meliloti, E. coli fabI, or Pseudomonas aeruginosa fabV. Furthermore, we validated that the deletion of fabI1 in S. meliloti triggered an increase in UFA production compared to the wild-type strain Rm1021. Conclusions In this study, we identified the ENR, encoded by the S. meliloti SMc00326 gene (fabI2), as playing a pivotal role in the biosynthesis of UFAs. Additionally, the FabI1 enzyme, encoded by SMc00005, was found to modulate the fatty acid composition within S. meliloti. Together, these discoveries establish a foundation for the development of a model that explains the significant contribution of FabI2 to the robust synthesis of UFAs in S. meliloti.